Validity and Reliability of Teacher-Made English Summative Test at Second Grade of Vocational High School 2 Palopo (Language Circle: Journal of Language and Literature, 2019)
This research aimed to find out the validity and reliability of the English summative test for the second grade of Vocational High School 2 Palopo. The research applied mix-method design (Qualitative-Quantitative). The researcher analyzed the data using validity and reliability formula by Suharsimi Arikunto and Kuder-Richardson’s. There were 40 multiple choice questions of English summative test. This research used expert judgement as validator to analyzed and commented the validity and reliability of English summative test made by the English teacher at second grade of Vocational high school 2 Palopo. The result indicated that the test items of English summative test at second grade of Vocational High School 2 Palopo had good content validity. Based on the percentage, the researcher found that the English summative test was 80% valid in terms of its conformity with the indicators. The items tests that represent the suggested indicators in the syllabus were 32 items and the inconformity items were 8 items. The reliability of English summative test was 0.6132. It means that the reliability of English summative test was in classification into the high level (0.60-0.799).